On Features of Self-Determination of Adolescent of Indigenous Peoples of Far North (Nenets Adolescents) - Y. Y. Lezina; T. M. Bostandzhiyeva (Научный диалог, 2017)
The article is devoted to the problem of forming of self-identity in Nenets adolescents. The relevance of the study of self-identity of adolescent of indigenous peoples of the North is determined by the ambiguity of the influence of social factors: on the one hand, macrosocial factors related to socio-political and socio-economic situation in the country, and on the other hand, microsocial factors as ethnic and national characteristics and the microenvironment in which a teenager is growing up. Attention is paid to analysis of peculiarities of formation of self-identity in the juvenile period of ontogenesis, related to the assimilation of values, life orientations, a picture of oneself, future goals and ways of professional and personal development. The problem of formation of ethnic identity of Nenets adolescents is considered from positions of influence of those socio-economic and political processes that led to the loss of language, traditions and customs, that are the important component of ethnic identity and self-determination. The article focuses on the initial marginality of self-determination of Nenets adolescent. Attention is paid to the problems of socio-cultural deprivation and uncertainty of further professional self-determination (after finishing school), faced by Nenets adolescents living in nation villages.